CRIMINALISTICS IN THE PERIOD BETWEEN WORLD WARS - Ibodullaev Saidmuhammad Rahmatullaevich (American Journals, 2023)
In this article we are talking about the fact that in the period between the two world wars for domestic criminology, the volume of accumulation of empirical material was increased, the task of disseminating forensic knowledge among specialists of professional bodies, practically creating manuals and manuals, was solved. And also the issue of the independent nature of forensic science was positively resolved, which, however, met with objections from some scientists.
Keywords: world wars, domestic criminalistics, crime investigation methodology, interrogation, interrogation investigation, criminal investigation, detective, criminal technique, sign, identification.